Phosphoinositide 3-Kinase/Akt Signaling and Redox Metabolism in Cancer - Koundouros, Nikos; Poulogiannis, George (Frontiers in Oncology, 2018)
Metabolic rewiring and the consequent production of reactive oxygen species (ROS) are necessary to promote tumorigenesis. At the nexus of these cellular processes is the aberrant regulation of oncogenic signaling cascades such as the phosphoinositide 3-kinase and AKT (PI3K/Akt) pathway, which is one of the most frequently dysregulated pathways in cancer. In this review, we examine the regulation of ROS metabolism in the context of PI3K-driven tumors with particular emphasis on four main areas of research. (1) Stimulation of ROS production through direct modulation of mitochondrial bioenergetics, activation of NADPH oxidases (NOXs) and metabolic byproducts associated with hyperactive PI3K/Akt signaling. (2) The induction of pro-tumorigenic signaling cascades by ROS as a consequence of PTEN and receptor tyrosine phosphatase redox-dependent inactivation. (3) The mechanisms through which PI3K/Akt activation confers a selective advantage to cancer cells by maintaining redox homeostasis. (4) Opportunities for therapeutically exploiting redox metabolism in PIK3CA mutant tumors and the potential for implementing novel combinatorial therapies to suppress tumor growth and overcome drug resistance. Further research focusing on the multi-faceted interactions between PI3K/Akt signaling and ROS metabolism will undoubtedly contribute to novel insights into the extensive pro-oncogenic effects of this pathway, and the identification of exploitable vulnerabilities for the treatment of hyperactive PI3K/Akt tumors.